BRIA PROJECT – A PUBLIC PRIVATE PARTNERSHIP TO IMPROVE FARMERS’ LIVELIHOOD - Sulaiman Ginting; Isnaini Jalil (UNEJ e-Proceeding, 2017)
Better Rice Initiative Asia (BRIA) Indonesia is a partnership program between public andprivate sector, known as the Public Private Partnership (PPP), funded by the public sector -namely the Ministry of Economic Cooperation and Development of Germany (BMZ) and BASFof the private sector, implemented by German International Cooperation (GIZ) and BASF toimprove the economic welfare through increased production and better market access.Within the implementation period (2015-2017), BRIA Indonesia is targetted to reach 6,700farmers from five chosen districts of two provinces; Langkat, Deli Serdang, Serdang Bedagai,and Simalungun (North Sumatra Province), and Jember (East Java Province). The project hasreached the total 3,540 farmers in 183 FFS at the selected locations. BRIA promotes theadoption of Good Agriculture Practices (GAP) of rice for sustainable increase in riceproductivity, and increasing the involvement of young people in the agricultural sector. It isdone through the establishment of Farmer Field School (FFS) at village level as rice farminglearning center applying Good Agriculture Practice (GAP). The FFS is a training systemapproach that aims to transfer technical and practical know-how and skills to rice farmersthrough technical training, physical demonstration in the field and learning by doingexercises. The project has identified four main technologies to improve farmers’ incomes andagricultural productivity, including seed technology, row-spacing ”legowo” planting method,balanced fertilization by using soil test kit (PUTS), and integrated pest management (IPM). BRIA Indonesia has also initiated to develop the seed grower business model to improve seedquality. The goal was to encourage farmers to become seed growers, and considering this as abusiness opportunity. In total around 150 farmers were trained by BRIA on how to producehigh quality seeds. These 150 farmers can support 17,000 hectares or 1,200 farmers,resulting in an increase in yield for these farmers. Aligned with those activities, a farmerdatabase has been created and used internally for managing and monitoring the processincluding farmer identity and farm profiles, production, technology and farming practicesadopted, geotagging and others. Furthermore, instead of its purpose as project monitoringand evaluation, the database system will be improved to support government policy on ricecrop insurance and financing facility for agriculture sector.